2015
DOI: 10.1508/cytologia.80.237
|View full text |Cite
|
Sign up to set email alerts
|

New Karyotypes in Some Species of Asteraceae from Turkey

Abstract: SummaryIn this study, chromosome numbers and morphologies are presented for four species growing naturally in Turkey. These species are Inula peacockiana (Aitch. & Hemsl.) Korovin, Cousinia boissieri Buhse, Scorzonera renzii Rech. f., Lactuca intricata Boiss. Chromosome number of studied species are Inula peacockiana 2n=20, Cousinia boissieri 2n=26, Scorzonera renzii 2n=14 and Lactuca intricata 2n=18. Also, karyotype analyses were made using the Bs200Pro Image Analysis Software. In addition, the karyotype asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Cytogenetical and karyotypic studies have revealed variations of chromosomes in size, morphology, and number in various clades of plant and animal species (Al-Dakan and Al-Saleh 2015, Al-Qahtani et al 2014, Arslan and Zima 2014, Bagane et al 2014, Çakmak and Koca 2014, Deshpande et al 2014, El-Esawi and Sammour 2014, Gholave et al 2014, Haroun and Alotaibi 2015, Jantarat et al 2014a, Kaewmad et al 2014, 2014c, Kantek et al 2015, Kasiroek et al 2014, Kaur and Singhal 2015, Khakhong et al 2014, Kumar et al 2015, Kumar et al 2014, Li et al 2015, Martin et al 2015, Miura and Iwatsubo 2014, Parai and Mukherjee 2014, Park 2015, Patawang et al 2014a, Phimphan et al 2015, Pierozzi and Baroni 2014, Pinthong et al 2014, Qumsiyeh et al 2014, Rezaei et al 2014, Samanta et al 2015, Sato et al 2015, Tahami et al 2014, Venkatesh and Munirajappa 2015, Venkatesh et al 2014, Walia et al 2015. Cytogenetical techniques including banding methods and FISH have revealed the evolutionary process in structural and number changes of chromosomes (Lombello and Pinto-maglio 2014…”
mentioning
confidence: 99%
“…Cytogenetical and karyotypic studies have revealed variations of chromosomes in size, morphology, and number in various clades of plant and animal species (Al-Dakan and Al-Saleh 2015, Al-Qahtani et al 2014, Arslan and Zima 2014, Bagane et al 2014, Çakmak and Koca 2014, Deshpande et al 2014, El-Esawi and Sammour 2014, Gholave et al 2014, Haroun and Alotaibi 2015, Jantarat et al 2014a, Kaewmad et al 2014, 2014c, Kantek et al 2015, Kasiroek et al 2014, Kaur and Singhal 2015, Khakhong et al 2014, Kumar et al 2015, Kumar et al 2014, Li et al 2015, Martin et al 2015, Miura and Iwatsubo 2014, Parai and Mukherjee 2014, Park 2015, Patawang et al 2014a, Phimphan et al 2015, Pierozzi and Baroni 2014, Pinthong et al 2014, Qumsiyeh et al 2014, Rezaei et al 2014, Samanta et al 2015, Sato et al 2015, Tahami et al 2014, Venkatesh and Munirajappa 2015, Venkatesh et al 2014, Walia et al 2015. Cytogenetical techniques including banding methods and FISH have revealed the evolutionary process in structural and number changes of chromosomes (Lombello and Pinto-maglio 2014…”
mentioning
confidence: 99%